Organisational responses to mitigate the effects of COVID-19 on healthcare workers: a qualitative case study from Bogotá, Colombia - Simon Turner; Natalia Niño; Carolina Segura; Natalia Botero-Tovar (BMC, 2021)
Abstract Background Healthcare organisations have undergone organisational change to respond to COVID-19. This pandemic has presented challenges for employee adjustment, with impacts on the availability and coordination of human resources in healthcare. This study aimed to characterise the organisational actions regarding the coordination of human resources in healthcare within Bogotá, Colombia, to respond to the COVID-19 pandemic. Methods We followed a case study approach to understand the response to the emergency taking into account the narratives of managerial actors who have been directly involved in the planning of guidelines oriented to face the pandemic or in the implementation of health services for COVID-19. Twenty-two interviews with multiple health system organisations within Bogotá were conducted between May and September 2020 and analysed thematically. Results Three themes emerged from the analysis of the interview data: to retain human resources, to implement actions to improve the mental and physical health of the healthcare workers, and to enhance healthcare workers knowledge, skills and availability to respond to COVID-19. Conclusions Organisational actions led by hospital managers to retain, protect, and train human health resources in the dynamic context of the COVID-19 pandemic were identified. Other system-wide organisations like scientific associations contributed to the coordination of human resources across hospitals to respond to COVID-19 in Bogotá, Colombia. The actions of hospital managers, and roles of system-wide intermediary organisations, in coordinating human resources need to be explored in other health system contexts facing COVID-19.